PHENOTYPIC AND GENETIC CORRELATIONS BETWEEN AGE AND WEIGHT AT FIRST SERVICE IN LOHI SHEEP - M. E. Babar; M. Abdullah; K. Javed; A. Ali; N. Ahmad (Journal of Animal and Plant Sciences, 2008)
Data on breeding and performance of 1003 ewes sired by 56 rams kept at the Livestock Production Research Institute, Bahadurnagar, Okara were analyzed by using Harvey’s Mixed Model Least Squares and Maximum Likelihood Computer Program. Phenotypic correlation between age and weight at first service was 0.304 which was significant indicating that weight at first service will increase with increased age at first service. Genetic correlation of - 0.266 ± 0.193 between age and weight at first service indicated a genetic antagonism between the two traits.
Keywords: Phenotypic and genetic correlations; age and weight at first service.